Challenges and advantages of implementing electronic dental records: A literature review (Research, Society and Development, 2025)
With the advancement of technology and innovation in various areas of health, including Dentistry, electronic medical records have emerged. They have expanded due to their ease, validity and reliability, being useful at both the public and private levels. This study sought to conduct a literature review on the use of electronic medical records in Dentistry, addressing their advantages, disadvantages and the main current evidence. Methodology: To this end, we searched the scientific literature, the PUBMED and Lilacs databases and the CAPES journal portal, reading a total of 88 articles in full and using 17 references to extract information for this study, including articles, monographs, theses and reference websites. Literature review: The literature has emphasized the use of electronic medical records showing its usefulness and are also important at the public health level and even for judicial authorities in the case of criminal and civil proceedings. In the dental field, it is important to make it clear that the development of electronic medical records for oral health requires adaptations when compared to standard medical records, requiring the incorporation of certain specialties, both for clinical, management and research purposes. This literature review indicated that the use of electronic medical records in Dentistry has been growing in Brazil and worldwide. It was found that their use has been applied in both public and private sectors, in the clinical and management areas, where in the last ten years there have been investments especially by the federal government in the SUS, with the emergence and implementation of e-SUS in several basic health units.